KEBERADAAN BATIK KLIWONAN DI KABUPATEN SRAGEN - Tiwi Bina Affanti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
Title of research: â€œExistence of Batik Kliwonanâ€. The research focused on: (1) appearance of pembatikan at rural area of Bengawan Solo (Kliwonan, Sidodadi, Pilang, Jabung, and Gedongan residence); and (2) dynamics of batik business by Batik Kliwonan communities. Cultural and historical approaches were used to solve these case that related to batik activities at rural area of Bengawan Solo (Sragen) until dynamics of Batik it self. It needs theories that related some cultures (river, farmer and aristocrat, cultural result and social-cultural) and histories to solve them. Research strategy tends to be descriptive research, with single case study. Data collected was qualitative data, which was used based on the informant, batik products, documents, also places and activities of making batik. Some technics of data collecting which were used are interview, observations and study about document. Research results were: (1) Existence of batik at rural area of Bengawan Soloâ€“Sragen was affected by river as medium of transportation and trade, need for pembatik at urban area, water as supporter in processing batik, and Sragen society need part time job; (2) dynamics of batik begin from craftman history, from employee until be owner of batik enterpreneur called Batik Kliwonan. When Batik Kliwonan specified as tourism target, its image was built by creative and visual strategies. Keywords: Batik, Kliwonan, Sragen